Chapter Zu slavisch-baltischen Konvergenzen (und ihr Fehlen) im Aspekt-Tempus-Bereich - Wiemer, Bjoern (Biblioteca di Studi Slavistici, 2023)
The article provides a survey of aspect-tense (AT) grams in (North) Slavic and Baltic, with some account of Finnic. More recently developed grams (bound morphology and constructions) are evaluated against a deeper diachronic and larger areal backdrop in order to assess the significance of contact as a factor contributing to convergence of Slavic and Baltic varieties in the AT domain. In fact, the amount of actually converging features related to grammatical oppositions in this area is quite small; these are: (i) Prominent parallels in the strict subject- vs. object-oriented division of perfects in Slavic (mainly Belarusian) rural varieties, which must have been supported by an ancient and very stable Baltic model. (ii) Suffixation patterns of stem derivation in Aukštaitian Lithuanian resembling Slavic secondary imperfectivisation. The reasons for a generally low level of mutual influence between Baltic and Slavic are subjected to some methodological discussion.